2020
DOI: 10.3389/fnmol.2020.583811
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Transcriptomic and Proteomic Profiling of Heterogeneity of Brain-Derived Microglia in Multiple Sclerosis

Abstract: Microglia are important for central nervous system (CNS) homeostasis and first to respond to tissue damage and perturbations. Microglia are heterogeneous cells; in case of pathology, microglia adopt a range of phenotypes with altered functions. However, how these different microglia subtypes are implicated in CNS disease is largely unresolved. Multiple sclerosis (MS) is a chronic demyelinating disease of the CNS, characterized by inflammation and axonal degeneration, ultimately leading to neurological decline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 166 publications
(273 reference statements)
1
9
0
Order By: Relevance
“…Together, this ensures that a positive signal within the cell truly represents a specific transcript of the decoded gene. Concerning sensitivity, Miedema et al reported smFISH to be one of the most sensitive spatial RNA detection methods and highly suitable for low abundance genes 46 , considering it to be the gold standard of spatial in-situ methods.…”
Section: Discussionmentioning
confidence: 99%
“…Together, this ensures that a positive signal within the cell truly represents a specific transcript of the decoded gene. Concerning sensitivity, Miedema et al reported smFISH to be one of the most sensitive spatial RNA detection methods and highly suitable for low abundance genes 46 , considering it to be the gold standard of spatial in-situ methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recent technological advances permitting analysis at the single-cell level (reviewed in Papalexi and Satija, 2018) have not only allowed for this distinction, but have also provided greater insight into the mechanisms underlying the vast cellular plasticity and heterogeneity of CNS-resident microglia (Masuda et al, 2019;Böttcher et al, 2020). These studies, which are reviewed extensively in Miedema et al (2020), provide additional evidence that discrete microglial subsets perform multiple, unique functions and contribute to MS/EAE disease pathogenesis through the temporal regulation of disease-and context-specific gene expression programs (Masuda et al, 2019;Böttcher et al, 2020).…”
Section: Microgliamentioning
confidence: 99%
“…Microglia are highly dependent on environmental signals to maintain their polarization. Given that such signals may vary across brain regions, it is notable that immune profiling of human brain microglia by single-cell proteomics revealed remarkable regional heterogeneity ( 185 ). Myeloid cells strategically located in close proximity to fenestrated blood vessels in the MBH may be able to sense metabolic factors including circulating lipids.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%